2014
DOI: 10.1007/s10653-014-9642-3
|View full text |Cite
|
Sign up to set email alerts
|

A measurement of summertime dry deposition of ambient air particulates and associated metallic pollutants in Central Taiwan

Abstract: The purpose of this study is to characterize metallic elements associated with atmospheric particulate matter in the dry deposition plate, total suspended particulate, fine particles, and coarse particles at Taichung Harbor and Gong Ming Junior High School (airport) in central Taiwan at a sampling site from June 2013 to August 2013. The results indicated that: (1) the average concentrations of the metallic elements Cr and Cd were highest at the Gong Ming Junior High School (airport), and the average concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
0
2
1
Order By: Relevance
“…These results indicated that there was no significant association between dry deposition velocity and wind speed of PM ( Fig 7a and 7b ). However, this result did not conform with the results of other studies [ 26 , 27 ] and the relevant explanations made by some physical models, such as firm theory and the resistance model [ 28 – 30 ]. Furthermore, wind speed could also influence the particles accumulation on leaves [ 31 ].…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…These results indicated that there was no significant association between dry deposition velocity and wind speed of PM ( Fig 7a and 7b ). However, this result did not conform with the results of other studies [ 26 , 27 ] and the relevant explanations made by some physical models, such as firm theory and the resistance model [ 28 – 30 ]. Furthermore, wind speed could also influence the particles accumulation on leaves [ 31 ].…”
Section: Discussioncontrasting
confidence: 96%
“…Furthermore, wind speed could also influence the particles accumulation on leaves [ 31 ]. Wind speed was the strongest meteorological factor, which influenced dry deposition velocity [ 26 ] and had a positive correlation with the dry deposition velocity of TSP [ 22 , 26 29 ]. The results of our study may have been affected by the low wind speed conditions that prevailed during the sampling period.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy metals are one of the most important pollutants emitted to the atmosphere due to their toxic effects on the environment and human health (Fang et al, 2015). Heavy metals may come from many different sources in urbanized areas, including vehicle emissions, industrial discharges and other activities (Talebi and Abedi, 2004).…”
Section: Introductionmentioning
confidence: 99%